LINGKUNGAN SOSIAL DAN KEPRIBADIAN PADA PEMBENTUKAN PERILAKU KONSUMEN TERHADAP BARANG MEWAH PALSU - Andini, Deviliandri Dwi; Rachmawati, Gina; Kurniaty, Dewi (LP2M Universitas Bina Bangsa, 2025)
The social environment and personality play a significant role in shaping consumer behavior toward choosing counterfeit luxury goods, a phenomenon increasingly capturing attention in the modern era. This study analyzes the influence of social environment and personality on consumer decisions to purchase counterfeit luxury goods in Indonesia. Using a quantitative approach, data from 200 respondents revealed that the majority, women aged 20-40, spend over Rp1,000,000 per month on luxury items, primarily through online shopping. Regression results show a determination coefficient (R²) of 0.448, indicating that 44.8% of the variation in purchase intention for counterfeit luxury goods is explained by social environment and personality variables, with the remaining 55.2% influenced by other factors. The findings underscore the importance of social pressure and the need for status in the decision to buy counterfeit items. The study’s implications suggest the necessity of educational campaigns emphasizing product authenticity to reduce demand for counterfeit goods